2021
DOI: 10.3389/fcell.2021.632445
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Function of Myosin-18, an Unconventional Class of the Myosin Superfamily

Abstract: Myosin is a diverse superfamily of motor proteins responsible for actin-based motility and contractility in eukaryotic cells. Myosin-18 family, including myosin-18A and myosin-18B, belongs to an unconventional class of myosin, which lacks ATPase motor activity, and the investigations on their functions and molecular mechanisms in vertebrate development and diseases have just been initiated in recent years. Myosin-18A is ubiquitously expressed in mammalian cells, whereas myosin-18B shows strong enrichment in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Mutation studies have shown that Dst-b is essential for strained muscle maintenance (Yoshioka et al, 2022). We have also found a node exclusion block in Myo18A, which is consistent with shorter annotated isoforms that are derived from an internal transcription start site (Guzik-Lendrum et al, 2013;Ouyang et al, 2021)…”
Section: Identification Of Coordinately Spliced Exon Blockssupporting
confidence: 82%
“…Mutation studies have shown that Dst-b is essential for strained muscle maintenance (Yoshioka et al, 2022). We have also found a node exclusion block in Myo18A, which is consistent with shorter annotated isoforms that are derived from an internal transcription start site (Guzik-Lendrum et al, 2013;Ouyang et al, 2021)…”
Section: Identification Of Coordinately Spliced Exon Blockssupporting
confidence: 82%
“…These observations further support an implication of Lurap1 in connecting actin cytoskeleton to cell adhesion. Given the importance of MYO18A and p190RhoGEF in the regulation of the actin-based contractile machinery in different cell types [ 37 , 38 , 39 ], it would be of interest to determine whether these Lurap1 interaction partners are also involved in epiboly movement.…”
Section: Discussionmentioning
confidence: 99%
“…The myosin‐XVIII family is represented by Myo18a and Myo18b, with the latter being found exclusively in vertebrates (Salamon et al, 2003). Initially identified by the presence of a PDZ domain in its N‐terminal region, the myosin‐XVIII class has more recently been defined by typical long N‐ and C‐terminal extensions (Ouyang et al, 2021).…”
Section: Myosin‐xviiimentioning
confidence: 99%
“…While most myosins are known for their ability to hydrolyze ATP into ADP and use the resulting energy to generate movement and tension along actin filaments, MYO18A and MYO18B have mutations in the regions coding for the motor domain responsible for ATP hydrolysis. In addition, biochemical assays have shown that Myo18a lacks ATPase activity (Guzik‐Lendrum, Nagy, Takagi, Houdusse, & Sellers, 2011; Ouyang et al, 2021; Taft et al, 2013). The matter is not entirely settled, though, as some reports have indicated that mutations in the Myo18a motor domain can turn the resulting protein into a dominant‐negative (Tan, Yong, Dong, Lim, & Leung, 2008), suggesting the motor domain may be active.…”
Section: Myosin‐xviiimentioning
confidence: 99%